Who benefited from Burundi's demobilization program? - D'Aoust, O; Sterck, O; Verwimp, P (Oxford University Press, 2016)
This paper assesses the impact of the demobilization, reinsertion and reintegration program in post-war Burundi. Two major rebel groups benefited from cash and in-kind transfers, the CNDD-FDD from 2004, and the FNL from 2010. We combine panel data of households collected in 2006 and 2010 with official records from the National Commission for Demobilization, Reinsertion and Reintegration. We find that the cash payments received by FNL demobilized households had a positive impact on consumption, nonfood spending and investments. The program also generated positive spillovers in the villages where FNL combatants returned. Ex-combatants indeed spent a large part of their allowance on consumption goods and clothing, thereby generating a short-run economic boom in villages. However, the long-run evolution of consumption indicators is negative for CNDD-FDD households, as well as for villages where CNDD-FDD combatants returned, suggesting that the direct impact and the spillovers of the program vanished in the long run.